Clarendon Press - April 24, 1986 - (:unkn) unknown (My University, 1986)
Microfilm provided by the Panhandle-Plains Historical Museum and Clarendon ISD.
The Clarendon Press was founded in 1972. In 1974, the newspaper merged with and absorbed the Donley County Leader and Clarendon News to become The Clarendon Press.
Keywords: Clarendon Press.; Clarendon (Tex.)--Newspapers.; Donley County (Tex.)--Newspapers.